Third Annual Conference of the Center for the Study of Islam and Democracy (American Journal of Islam and Society, 2002)
On April 6-7, 2002, the Center for the Study of Islam and Democracy(CSID) held its Third Annual Conference on the theme "Democratizationand Political Violence in Muslim Societies" just outside Washington, DC,at the Sheraton Crystal City Hotel in Arlington, Virginia. The conferencewas cosponsored by the Institute for Global Cultural Studies, StateUniversity of New York, Binghamton, NY, and the International Institute ofIslamic Thought (IIIT), VA.The conference got off to a lively start on Saturday morning with PanelOne: "Islam and Political Participation: Ideals, Actors, and Processes"which was chaired by Charles Butterworth of the University of Maryland,College Park. Asma Afsaruddin of the University of Notre Dame, IN,explored links between early Islamic discourse of the Khulafa 'a/-Rashidunera and modern Islamic conceptions of leadership in "Medieval IslamicDiscourse on Legitimate Leadership and its Modern Implications."Wanda Kruse of the University of Guelph, Canada, discussed theunderestimated role played by non-governmental political actors in theMiddle East in "Civil Society in the Democratization Process: A CaseStudy on Cairo Islamic Women's Organizations." Imad-ad-Dean Ahmad ofthe Minaret of Freedom Institute, MD, focused on the cases where democraticdecision-making in government enhanced law and order in earlyIslamic history in "The Anti-Correlation between Democracy and PoliticalViolence in the Experience of the Khulafa' al-Rashidun." Moataz A. Fattahof Cairo University closed the panel with an overview of empirical evidenceabout Muslims' attitudes towards democracy in "The Compatibilty ofMuslims' Beliefs and Democracy: Survey Results."Panel Two which was chaired by Jamal Barzinji of the InternationalInstitute of Islamic Thought had as its theme "Western Democracies andAuthoritarian Muslim Regimes: Understanding the Relationship." AuwaluHamisu Yadudu of Bayero University in no, Nigeria, analyzed the Shari'a ...